Scolionema sanshin sp. n., a new species (Hydrozoa, Limnomedusae, Olindiidae) from the Ryukyu Archipelago, southern Japan - Toshino, Sho (Zootaxa, 2017)
A new species of hydrozoan jellyfish belonging to the order Limnomedusae is reported from the Ryukyu Archipelago, Southern Japan. The species belongs to the genus Scolionema, which prior to this study includes just a single valid species, S. suvaense. This name, however, has several junior synonyms and considerable diversity has been reported for different populations from Mediterranean, Indian ocean and Pacific ocean localities, including Central Japan. The species described in this paper, Scolionema sanshin sp. n., can be differentiated from all other described populations of Scolionema based on shape of gonad, number of tentacles of its medusa stage, and/or genetic sequences. A discussion of the diversity presently united under the name S. suvaense suggests that additional work is necessary to clarify the true number of Scolionema species.